Formulation and characterization of nanostructured lipid carriers of curcumin and their development in topical gel preparations for drug delivery systems - Garnadi Jafar; Choerrunisa Choerrunisa; Ika Kurnia Sukmawati; Al-fira Putriyanti (Science Midwifery, 2026)
Curcumin is a bioactive compound derived from Curcuma longa with anti-inflammatory and antioxidant activities; however, its topical application is limited due to poor solubility and stability. The development of nanoparticle-based delivery systems such as Nanostructured Lipid Carriers (NLC) can enhance drug stability and skin penetration. This study aimed to formulate curcumin-loaded NLC, evaluate its physicochemical characteristics, and develop a gel dosage form based on the optimized NLC formulation. The research methods included preliminary solubility testing of curcumin in various lipid and surfactant components, compatibility analysis using Differential Scanning Calorimetry (DSC), formulation of five NLC formulations using hot homogenization and probe sonication methods, and characterization including particle size, polydispersity index, zeta potential, entrapment efficiency, and morphology using Transmission Electron Microscopy (TEM). The selected NLC formulation was subsequently incorporated into a gel system and evaluated for pH, viscosity, and spreadability. The results demonstrated that the curcumin NLC exhibited nanoscale particle size with relatively uniform distribution, stable zeta potential values, and high entrapment efficiency. TEM analysis confirmed spherical particle morphology. The NLC-based gel formulation showed acceptable physicochemical properties, including skin-compatible pH, suitable viscosity, and optimal spreadability. In conclusion, curcumin was successfully formulated into an NLC system and further developed into a topical gel formulation with promising physicochemical characteristics as a lipid-based drug delivery system.